Experimental study of heat transfer enhancement for molten salt with transversely grooved tube heat exchanger in laminar-transition-turbulent regimes. (5th March 2018) - Chen, Y.S.; Tian, J.; Fu, Y.; Tang, Z.F.; Zhu, H.H.; Wang, N.X.
Highlights: Heat transfer of molten salt in transversely grooved tube is experimentally studied. Effects of Re and Pr on heat transfer enhancement characteristics are studied. Transversely grooved tube significantly enhances heat transfer performance. Transversely grooved tube expedites transition from laminar flow to turbulent flow. Heat transfer correlations of molten salt in transversely grooved tube are proposed. Abstract: In an effort to develop a heat transfer enhancement technique for molten salt in heat exchanger, experiments are carried out to evaluate the heat transfer performance of transversely grooved tube using molten salt as the hot fluid flowing through the inner concentric tube within the Reynolds number from 300 to 60, 000 and Prandtl number from 11 to 27. The effects of Reynolds number and Prandtl number on the thermal-hydraulic behavior in laminar, transition and turbulent flow are studied. Results show that transversely grooved tube will significantly enhance the heat transfer performance of molten salt and meanwhile decrease the critical Reynolds numbers of the transition from laminar flow to turbulent flow. For laminar flow and transition flow, heat transfer enhancement ratio relative to the smooth tube varies with the changing of Reynolds number and Prandtl number. While for the turbulent flow, the enhancement effect is almost independent on Reynolds number and Prandtl number. Finally, heat transfer correlations of molten salt in transversely grooved tube are proposed depending upon the flow regime and have good agreement with experiment data. Experimental results will provide valuable reference and greatly contribute to the practical design of molten salt heat exchanger with heat transfer enhancement techniques.